(untitled) (Research, Society and Development, 2021)
In tropical regions presenting severe seasonality, the reproductive activity of many species occurs during the most appropriate periods of the year. Therefore, several physiological and behavioral adjustments are needed during their reproductive cycle. This study aims to evaluate possible changes in histologic and morphometric parameters of the ovaries as well in estrogen and progesterone plasma levels of Leptodactylus macrosternum females and their relationship with temperature and precipitation. Specimens were collected in the Horto Florestal Olho d’Água da Bica - HFOB (06°49´20’’S/36°15´85’’W) area in the municipality of Cuité, brazilian semiarid, every 15 days, only between the months of May to August and November to December. The quantification of population density of oocyte types and dosages of progesterone and estrogen levels were used to determine the reproductive activity of the species. Population densities of oogonia and oocyte II did not vary significantly during the months in which the animals were sampled. Population densities of oocyte I was significantly higher during the months of June (p= 0.04) and August (p= 0.03). The highest values for the population density of oocyte III and IV were found in the months of May (p=0.04) and June (p=0.04). The amounts of estrogen concentrations (pg / ml) and progesterone (pg / ml) did not change significantly over the sampling periods. The population density of the types of oocytes III and IV showed dependence on the variation in rainfall.